Venice Commission: the role in the process of international and national law interpretation. - Toronchuk, Ivan; Karvatska, Svitlana; Manyk, Alyona (Editura ASE, 2021)
The article aims to study the Venice Commission's role as one of the leading international law interpreters. This role has gradually strengthened in the process of scientifically substantiated promotion of legal norms and standards concerning democracy, human rights, and the rule of law. Using system-structural, formal-legal, comparative-legal, empirical, and anthropological methods, one has drawn essential conclusions regarding implementing the Venice Commission's interpretive activities. As a result, it has been proved that the nature of the Venice Commission's interpretive activity demonstrates the existence and growing contradiction between the prevailing interpretive practice at the supranational level and the provisions of the classical theory of law interpretation. Ukraine's ongoing dialogue with the Venice Commission is vital to develop and improve legislation, especially laws, implementing new constitutional provisions on justice, the drafts of which have already been designed or are being developed, as well as indubitable compliance with these laws. Venice Commission's general documents should be for the Ukrainian legislator the source to base the preparation of relevant legislation.
Keywords: Venice Commission; subject of interpretation; interpretive practice; international and national law; legal norms and standards